Literature Review on the Implementation of National Health Insurance (JKN) in Improving Access and Efficiency of Health Service Administration in Indonesia - Putri Mendriani; Khairunnisa, Khairunnisa; Gurning, Fitriani P. (Sean Institute, 2025)
The implementation of the National Health Insurance (Jaminan Kesehatan Nasional - JKN) in Indonesia has been a critical effort towards achieving universal health coverage, aiming to provide affordable and accessible healthcare for all citizens. This research evaluates the effectiveness of JKN in improving healthcare access and administrative efficiency. The study utilizes a qualitative approach, analyzing secondary data from various health reports and government publications to assess the progress and challenges faced by the JKN system. Key aspects evaluated include the coverage expansion, technological advancements like the Mobile JKN app, and the collaboration with healthcare providers. The results show that JKN has successfully increased healthcare accessibility, with over 98% of the population enrolled, thus contributing to the country's Universal Health Coverage status. However, challenges remain, particularly in the equitable distribution of healthcare facilities, especially in remote and underserved areas. Additionally, administrative inefficiencies, such as delays in claims processing and the growing financial burden, require continuous monitoring and reform. The study concludes that while JKN has made significant strides in expanding access to healthcare, further improvements in the distribution of healthcare facilities, operational efficiency, and sustainable financing mechanisms are essential to ensure that JKN can continue to meet the health needs of Indonesia's diverse population in the long term.